1997
DOI: 10.2307/2963469
|View full text |Cite
|
Sign up to set email alerts
|

Primary-Productivity Gradients and Short-Term Population Dynamics in Open Systems

Abstract: We present three models representing the trophic and behavioral dynamics of a simple food chain (primary producers, grazers, and predators) at temporal scales shorter than the scale of consumer reproduction, and at the spatial scales typically employed in field experiments. These models incorporate flexible behavioral responses of organisms to their predators and resources in spatially heterogeneous environments that are open to immigration and emigration. The basic models include passive immigration at all tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 52 publications
1
71
0
Order By: Relevance
“…Vertical bars denote 1 SE increase in grazer growth or density in streams (Hill et al 1995), lower productivity of biofilms at forested locations may have contributed to the overall lower invertebrate biomass at those sites. Moreover, models of open systems dominated by mobile consumers (e.g., Deleatidium) that decrease emigration as resource abundance increases predict that abundance will increase at all trophic levels with an increase in resource availability (Nisbet et al 1997). In our case, difference in the productivity of biofilms is unlikely to be the only factor involved in determining consumer abundance because substantial differences in primary production at open sites would be required to overshadow the large differences in standing crop associated with trout.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vertical bars denote 1 SE increase in grazer growth or density in streams (Hill et al 1995), lower productivity of biofilms at forested locations may have contributed to the overall lower invertebrate biomass at those sites. Moreover, models of open systems dominated by mobile consumers (e.g., Deleatidium) that decrease emigration as resource abundance increases predict that abundance will increase at all trophic levels with an increase in resource availability (Nisbet et al 1997). In our case, difference in the productivity of biofilms is unlikely to be the only factor involved in determining consumer abundance because substantial differences in primary production at open sites would be required to overshadow the large differences in standing crop associated with trout.…”
Section: Discussionmentioning
confidence: 99%
“…Most models of food chains have been developed for closed systems, but many systems are open to immigration and emigration of organisms, which can significantly affect predator impact (e.g., Cooper et al 1990). Few population models have investigated the simultaneous effects of predators and resource supply on the dynamics of open systems (Wootton and Power 1993;Nisbet et al 1997;Diehl et al 2000). In contrast to traditional food-chain theory, some models of open systems predict that densities at all trophic levels will increase with enrichment (Nisbet et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility that patchy disturbances can affect the longterm distribution of mobile stream organisms has recently gained some theoretical support, as well. Nisbet et al (1997) modelled invertebrate grazer dynamics in lotic grazer-algae systems and showed that patches can develop persistent differences in grazer densities depending on the initial conditions in the patch and grazer immigration from adjacent patches.…”
Section: Discussionmentioning
confidence: 99%